1986
DOI: 10.1007/bf01314149
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell infection and thrombosis in paralysis caused by equid herpesvirus-1: Equine stroke

Abstract: Eight mares were infected with equid herpesvirus-1 subtype 1 isolated from a case of equine paresis. In two mares killed at 4 d.p.i. immunofluorescence showed endothelial cell infection together with thrombosis in the rete arteriosus of the nasal mucosa and also in the spinal cord of one of these mares. Circulating platelet counts in the other six mares fell as early as 2 d.p.i. and remained depressed for seven days. Circulating immune complexes started to appear at 2 d.p.i., reached maximum levels at 10 d.p.i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
136
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(149 citation statements)
references
References 17 publications
10
136
0
3
Order By: Relevance
“…Therefore EHV-9 will possess pathogenicity in the horse. The clinical symptoms and antibody responses of EHV-9 inoculated horses were almost identical to primary EHV-1 infection of horses with EHV-4 anamnestic infection [9]. The antibody response of H1 and H2 indicated that both of the horses had experience of previous infection with EHV-4.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore EHV-9 will possess pathogenicity in the horse. The clinical symptoms and antibody responses of EHV-9 inoculated horses were almost identical to primary EHV-1 infection of horses with EHV-4 anamnestic infection [9]. The antibody response of H1 and H2 indicated that both of the horses had experience of previous infection with EHV-4.…”
mentioning
confidence: 60%
“…The histopathological changes caused by EHV-9 were partially resembled to those of EHV-1 infected horses showing paresis [1,3,9,12,13,23]. Common features between EHV-9 encephalitis and EHV-1-associated meningoencephalomyelitis were cellular reaction including perivascular cuffing and glial reaction.…”
mentioning
confidence: 99%
“…However, eCG was not mitogenic and its ability to reactivate was independent of IL-2 mediation. The persistence of latent EHV-1 in T lymphocytes and its reactivation by eCG is consistent with EHV-1 infecting the endothelial lining of the endometrium in pregnant mares (Edington et al, 1986 ;Smith et al, 1992), particularly when abortion has occurred weeks or months after detectable viraemia (Gleeson & Collins, 1980). The evidence from culturing separate leukocyte populations indicates that both IL-2 and eCG reactivated EHV-1 indirectly.…”
Section: Discussionmentioning
confidence: 89%
“…During the viraemia EHV-1 has been isolated for up to 3 weeks postinfection from peripheral blood mononuclear cells, predominantly from T lymphocytes and to a lesser extent monocytes (Bumgardner et al, 1982 ;Kydd et al, 1994). This cell-associated viraemia in an acute infection has been shown to be a prerequisite for abortion and paresis by initiating replication of EHV-1 in endothelial cells in the pregnant uterus and CNS (Patel et al, 1982 ;Edington et al, 1986Edington et al, , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that differences in pathogenicity correlate with the ability to disseminate to and infect vascular endothelial cells in the uterus and central nervous system (Edington, Bridges, & Patel, 1986; Mumford et al., 1994; Patel, Edington, & Mumford, 1982; Platt, Singh, & Whitwell, 1980). Viruses carrying the A2254G neurological marker are thought to replicate to a higher level and induce a longer‐lasting viraemia than those lacking it (Allen & Breathnach, 2006).…”
Section: Introductionmentioning
confidence: 99%